Histopathological Responses of the Heart, Liverand Kidney to Calliandra Portoricensis Extractsin Wistar Rats Challenged with Venom of EchisOcellatus - Onyeama HP, Ebong PE, Eteng MU, Igile GO, Ibekwe HA, Ofemile PY (Journal of Applied Pharmaceutical Science)
This study was designed to evaluate the efficacy of Calliandra portoricensis extracts in ameliorating the histopathological changes in the heart, liver and kidney of wistar rat challenged with venom of Echis ocellatus. A total of 30 rats were randomly assigned into 5 treatment groups of 6 rats each. Group 1 (control) received nothing. Group 2 received 200μg venom/rat. Groups 3, 4 and 5 received, in addition to the same amount of venom, 0.5 ml of 100mg/100g body weight of rat as “antidote” concentration 4 hours after the administration of the venom. The dosages of the venom and the extracts were administered intramuscularly and after 4 hours the heart, liver and kidney were harvested for histopathological study of the changes in these organs. The groups treated with the extracts showed reduction in tissue injury compared to the venom alone, though not as good as the control group. This reduction is more marked in treatment group 4, which is polyphenol-rich and which is believed to be the component that is involved in complexation with the venom. This implies a restoration of these organs to a near normal state after the viperian envenomation.
Keywords: Histopathological,Venom,C.portoricensis,Heart,Liver,Kidney